Development of a Google Forms-Based Five-Tier Diagnostic Test for Identifying Misconceptions in Modern Physics - Sri Winarni; Vini Asnidar; Abdul Halim; Nurulwati; Musdar; Teuku Muhammad Hary Ramadhan (JTP - Jurnal Teknologi Pendidikan, 2026)
Misconceptions in modern physics concepts such as X-rays, the photoelectric effect, the Compton effect, pair production, and photon–gravity interactions remain prevalent among students and are difficult to detect using conventional assessments. This study aims to develop and implement a Five-Tier diagnostic instrument based on Google Forms to identify students’ misconceptions in modern physics learning. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The instrument was validated by subject matter and evaluation experts and tested on 14 students and two physics education lecturers. Data were collected through validation sheets, lecturer response questionnaires, instrument practicality questionnaires, and Five-Tier diagnostic tests. Data analysis was conducted descriptively and quantitatively using content validity analysis, empirical validity testing, Cronbach’s Alpha reliability testing, and percentage analysis. The results indicate that the instrument has very high content validity (CVL = 1.00; IRA = 1.00), adequate empirical validity and reliability (α = 0.54–0.64), and a very high level of practicality, as reflected by lecturer responses (92.50%) and instrument practicality (90.5%). The implementation results reveal that students’ misconceptions are most dominant in the Compton effect and pair production topics. Therefore, the developed Five-Tier diagnostic instrument is feasible and effective as a digital diagnostic assessment in modern physics learning and can serve as a practical reference for future development of technology-based diagnostic instruments.